The labor-managed firm, Herbert Gintis, and me - Dow, Gregory K. (Frontiers in Behavioral Economics, 2025)
During 1990–96, Herbert Gintis co-authored an influential series of journal articles and book chapters with Samuel Bowles on the nature of the capitalist economy and the prospects for labor-managed firms (LMFs). Their theoretical model highlighted the lack of external contract enforcement in the labor and capital markets. Specifically, it is hard to have legally enforceable contracts about the effort of workers or the risks taken by borrowers. Hence, these relationships often rely upon contingent renewal, where the employer or lender offers an enforcement rent and threatens to end the relationship if unsatisfactory behavior is detected. The model suggested that LMFs would have advantages in the labor market but disadvantages in the capital market. Here I review the Bowles and Gintis model, compare it with research of my own, and conclude that the main empirical predictions about LMFs made by Bowles and Gintis have stood the test of time.